Epitope Location on Tissue Factor Determines the Anticoagulant Potency of Monoclonal Anti-tissue Factor Antibodies - Kirchhofer, Daniel; Moran, Paul; Chiang, Nancy; Kim, Jin; Riederer, Markus A.; Eigenbrot, Charles; Kelley, Robert F. (Thrombosis and Haemostasis, 2000)
Tissue factor (TF), the cellular cofactor for the serine protease factor VIIa (F. VIIa), triggers blood coagulation and is involved in the pathogenesis of various thrombosis-related disorders. Therefore, agents which specifically target tissue factor, such as monoclonal antibodies, may provide promising new antithrombotic therapy. We mapped the epitopes of several anti-TF antibodies using a panel of soluble TF mutants. They bound to three distinct TF regions. The epitope of the 7G11 antibody included Phe50 and overlapped with a TF-F. VIIa light chain contact area. The common epitope of the antibodies 6B4 and HTF1 included residues Tyr94 and Phe76 both of which make critical contacts to the catalytic domain of F. VIIa. The antibodies D3 and 5G6 had a common epitope outside the TF-F. VIIa contact region. It included residues Lys165, Lys166, Asn199, Arg200 and Lys201 and thus overlapped with the substrate interaction region of tissue factor. The antibodies 5G6 and D3 were potent anticoagulants when infused to flowing human blood in an ex-vivo thrombosis model. Plasma fibrinopeptide A levels and fibrin deposition were completely inhibited. In contrast, 6B4 was a weak inhibitor in this ex-vivo thrombosis model, and HTF1 displayed no inhibition at all. These disparate activities were also reflected in TF-dependent F. X activation assays performed with human plasma. The potency differences could neither be explained by the determined binding affinities nor by the on-rates of antibodies. Therefore, the results suggest that antibody binding epitope and hence the particular mechanism of inhibition, is the main determinative factor of anticoagulant potency of anti-TF antibodies.
Keywords: Tissue factor; tissue factor mutation; coagulation; factor VII; monoclonal antibodies